2020
DOI: 10.32800/abc.2020.43.0055
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of jaguars (Panthera onca) and pumas (Puma concolor) in a tropical forest in south–eastern Mexico

Abstract: The biological ranges of the jaguar (Panthera onca) and puma (Puma concolor) overlap in the Yucatan Peninsula, corresponding to the most important population of jaguars in Mexico. The goal of this study in the El Eden Ecological Reserve (EER) was to investigate the factors that permit these two predators to coexist in the dense vegetation of medium–stature tropical forest and secondary forest in the north–eastern Yucatan Peninsula. We assessed their spatial and temporal overlap using Pianka’s index, and evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Spatiotemporal avoidance between pumas and jaguars is well documented (Seymour, 1989). In the Yucatan, Ávila–Nájera et al (2020) showed time of day to be the best predictor for the coexistence of these two cats, whereas in Belize, Harmsen et al (2009) found that pumas and jaguars avoided using the same place at the same time. Pumas in our study visited cenotes at a different time to jaguars and appearance at the same cenote by the two species was separated by several weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatiotemporal avoidance between pumas and jaguars is well documented (Seymour, 1989). In the Yucatan, Ávila–Nájera et al (2020) showed time of day to be the best predictor for the coexistence of these two cats, whereas in Belize, Harmsen et al (2009) found that pumas and jaguars avoided using the same place at the same time. Pumas in our study visited cenotes at a different time to jaguars and appearance at the same cenote by the two species was separated by several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Jaguar visitations at cenotes included some long bouts of rest within the cave environment in the hottest part of the day. In the Yucatan, jaguars are primarily crepuscular and nocturnal (Ávila–Nájera et al, 2020; Chávez et al, 2007). We only recorded 10 independent events of jaguars at cenotes, but of these, eight were during the middle of the day, while the four records of jaguars in the forest were at night.…”
Section: Discussionmentioning
confidence: 99%
“…Human activities are kinds of economic, recreational, or illegal activities carried out by humans that directly affect jaguar presence or biological processes within jaguar range (Carvalho et al 2015;Jordan et al 2016;Jędrzejewski et al 2017;Silva et al 2018;Ávila-Nájera et al 2019;Ávila-Nájera et al 2020). For such human activities 11 metrics were identified, including level of protection, distance to protected areas, cattle density, human activities, hunting pressure, forest loss, human footprint, distance to tourism, number of dams, fires, and indigenous communities nearby (Table 3).…”
Section: Anthropogenic Variablesmentioning
confidence: 99%